Adaptive design methods in dialysis clinical trials: a systematic review protocol. Issue 8 (27th August 2020) - Judge, Conor; Murphy, Robert P; Cormican, Sarah; Smyth, Andrew; O'Halloran, Martin; O'Donnell, Martin
Abstract : Introduction: Adaptive design methods are a potential solution to improve efficiency of clinical trials but their uptake in dialysis is unknown. We aim to investigate the use of adaptive design methods in dialysis clinical trials and to cultivate further adoption of adaptive design methods by the nephrology community. Methods and analysis: We will adhere to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines and the Cochrane Collaboration Handbook. We will perform a literature search through MEDLINE (PubMed), EMBASE and CENTRAL, a detailed data extraction of trial characteristics and a narrative synthesis of the data. There will be no language restrictions. We will estimate the percentage of adaptive clinical trials per year in dialysis. Subgroup analysis will be performed by dialysis modality, funder and geographical location. Ethics and dissemination: Ethical approval will not be required for this study as data will be obtained from publicly available clinical trials. We will disseminate our results in a peer-reviewed publication. PROSPERO registration number: